Cytogenetics and molecular study of P53 gene in liver cancer diagnosed in Erbil city using de novo sequencing method - Ismail, Nadhum J. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Liver cancer is the sixth most frequent cancer and the second leading cause of cancer death through the world. The first objective of the present study is to know the chromosomal aberrations in peripheral blood of liver cancer patients. The present study was carried out on 50 patients who were suffering from liver cancer in Erbil city and 25 healthy individuals as a healthy group in both sex and different age groups. The second objective of the present study is to know the mutations in TP53 tumor suppressor gene, so molecular study was carried out on 18 patients who were suffering from liver cancer in Erbil city and 1 healthy individual as a control group. Detection a mutation in TP53 gene in peripheral blood cells may be helpful to the diagnosis of liver cancer, especially to the accurate staging of liver cancer. Additionally, cytogenetic study followed by molecular analysis of recurring chromosome changes has facilitated the identification of crucial ontogenesis and tumor suppressor genes. The mechanism of liver carcinogenesis involve multiple endogenous and exogenous genetic alterations, so many factors contribute to its development such as genetic factors, Hepatitis Band C virus infections, smoking habit and alcohol habit. Other factors was also studied included patient gender and age. The results of the present study suggest that highest value of chromosomal aberrations was (Dicentric chromosome) which occurred in males at fifth age group (65-74) , also shown that most patients are males at age group(65-74), most of them have smoking , alcohol habit and Hepatitis B viral infection . From the study of TP53 gene, we observed mutation in exon 7 which was deletion of nitrogen base G , just before the coding region , which represent splice- site mutation.